A Comprehensive Methodology for Estimating Yearly Plastic Pollution Loads in Rivers - Stephanie B. Oswald; Esmee S. Oldenhof; Ad M. J. Ragas; Margriet M. Schoor; Frank P. L. Collas (Water, Air, & Soil Pollution, 2026)
Plastic pollution in freshwater systems represents a major global concern, as rivers serve as critical pathways between land-based sources and marine environments. Yet, inconsistencies are observed between estimated plastic inputs from land and concentrations in the ocean. Despite growing monitoring efforts, the lack of standardized methods and the use of diverse metrics for quantifying plastic pollution hamper direct comparisons across studies and limit comprehensive assessments. In this study, we developed a method for quantifying yearly macro- and mesoplastic load, incorporating different metrics. By integrating statistical analysis, the method accounts for variability in plastic concentrations and discharge rates. Subsequently, this methodology was applied to the Rhine and Meuse rivers in the Netherlands. The findings of this study indicate a spatial variability in plastic concentrations. The mean annual load of macro- and mesoplastics (items > 0.5 cm) in the Rhine was highest at Lobith, located at the Germany–Netherlands border (331 million items/year), decreasing downstream to 206 million items/year at Tiel. Similarly, in the Meuse, higher loads were observed at Eijsden, at the Belgium–Netherlands border (73 million items/year), than further downstream at Sambeek (62 million items/year), while particles in the 5–6 mm size range are likely underrepresented due to the 6 mm mesh size of the sampling net. Correspondingly, the mean annual surface area load of macro- and mesoplastics in the Meuse showed a downstream decrease, with mean values declining from 71,641.63 m 2 /year at Eijsden to 30,714.92 m 2 /year at Sambeek. The methodological approach enables the quantification of plastic loads, providing important insights into the dynamics of plastic pollution in river systems. This allows for predictions of future plastic quantities in the Rhine-Waal and Meuse rivers under different emission scenarios and measurement units.

Distribution, scale, and drivers of mass mortality events in Europe's freshwater bivalves - Daniel A. Cossey; Maria Urbańska; Ronaldo Sousa; Juergen Geist; Anna Maria Labecka; Şebnem Atasaral; Maciej Bonk; Liliya Bylyna; Frank P. L. Collas; Daniel Daill; Andreas H. Dobler; Noé Ferreira‐Rodríguez; et al. (Conservation Biology, 2026)
Mass mortality events (MMEs) are decimating populations and compromising key ecosystem functions around the globe. One taxon particularly vulnerable to MMEs is freshwater bivalve mollusks. This group has important ecosystem engineering capacities and includes highly threatened and highly invasive taxa. Thus, MMEs of freshwater bivalves have important implications for conservation and ecosystems. Despite this, little is known about the magnitude, frequency, duration, distribution, and causes of freshwater bivalve MMEs. Using a questionnaire, we compiled data from 239 reports describing freshwater bivalve MMEs across 22 European countries since 1960. With these data, we analyzed trends in MME timing, location, and magnitude; identified the species affected; and evaluated the suggested causes (including reporter certainty). We found that the frequency of reports of MMEs increased each year, MMEs affected a broad range of species, clear geographical patterns linking certain causes to specific locations were lacking, factors related to drying and habitat destruction predominated suggested causes, and considerable uncertainty surrounded the causes of many MMEs, particularly those associated with potential pollutants and disease agents. Based on our findings, we recommend the standardization of many aspects of MME research (e.g., reporting and recovery assessment protocols), increased surveying for MMEs, further investigation into the causes of MMEs, especially those with significant uncertainty, and immediate actions to improve waterbody management, mitigate the effects of high temperatures, and further protect freshwater bivalves through the development and implementation of appropriate management actions and legislation.

Development of biochar-immobilized Bacillus subtilis BEIB-18 for hexavalent chromium (Cr(VI)) bioremediation in aqueous medium - V. A. Schommer; M. T. Nazari; A. P. Vanin; D. D. C. Krein; N. Melo; L. F. dos Santos; G. L. Dotto; V. Ferrari; L. M. Colla; A. Dettmer; J. S. Piccin (International Journal of Environmental Science and Technology, 2026)

Evaluation of riverine macro- and mesoplastic monitoring approaches - Stephanie B. Oswald; Paul Vriend; Ad M. J. Ragas; Margriet M. Schoor; Frank P. L. Collas (Environmental Monitoring and Assessment, 2026)
Globally, plastic pollution in aquatic environments has become an emerging concern. A multitude of monitoring techniques have been used to collect information on the presence of macroplastics (> 25 mm) and mesoplastics (> 5 mm ≤ 25 mm) in river systems. The differences between these methodological approaches, combined with limited knowledge of the fundamental processes that affect plastic presence and detection ability, lead to a lack of standardization between methods and limit comparisons of quantitative data on plastic pollution among studies. This study investigates how different monitoring approaches, e.g., larvae net, trawl net, and stow net, affect the observed abundance and composition of macro- and mesoplastics in the Rhine-Waal Rivers. Additionally, we performed a SWOT analysis highlighting the strengths, weaknesses, opportunities, and threats of the three methods. During trawl net and stow net monitoring, more unique macro- and mesoplastics categories were found in comparison with simultaneous larvae net monitoring. However, while mean macroplastic concentrations were higher in the stow net samples (1.22 × 10 –3 items/m 3 ) than in the larvae net (0.91 × 10 –3 items/m 3 ), mesoplastics concentrations were significantly higher in the larvae net samples (6.91 × 10 –3 items/m 3 ) compared to those recorded with the stow net (1.15 × 10 –3 items/m 3 ), indicating that the size plastic recovery rates depend on the sampling technique. The SWOT analysis pointed towards a better overall performance of the trawl net. The outcome of the current study can be used to support policymakers, industry, and the scientific community in developing successful monitoring strategies for macro- and mesoplastics pollution in rivers. The SWOT analysis may facilitate the choice of the approach that best aligns with the specific monitoring goals and the environmental conditions of the target area.

Navigating the stormy seas of building ‘trust’ as a boundary organisation connecting marine science with policy and management - C. Cvitanovic; R.J. Shellock; D.B. Karcher; P. Tuohy; M. Mackay; E.I. van Putten; Marta Ballesteros; M. Dickey-Collas (Ocean & Coastal Management, 2024)

Carbon-to-nitrogen ratios on laccase and mushroom production of Lentinus crinitus - I. M. Colla; O. B. Q. de O. Filho; M. B. D. Bertéli; J. D. S. de Freitas; K. V. Avelino; S. P. Ruiz; J. S. do Valle; G. A. Linde; N. B. Colauto (International Journal of Environmental Science and Technology, 2023)

Assessing Habitat Suitability for Native and Alien Freshwater Mussels in the River Waal (the Netherlands), Using Hydroacoustics and Species Sensitivity Distributions - N. Y. Flores; F. P. L. Collas; K. Mehler; M. M. Schoor; C. K. Feld; R. S. E. W. Leuven (Environmental Modeling & Assessment, 2022)
Longitudinal training dams (LTDs) in the river Waal are novel river training structures that protect the littoral zone from the adverse effects of navigation providing new habitats for riverine macroinvertebrates. In order to inform river management and to better understand their ecological value for native and alien mussel species, it is important to assess the habitat suitability of the protected LTD shore channels. We applied spatial hydroacoustics surveys consisting of side-scan sonar (SSS) and acoustic Doppler current profiler (ADCP) of the substrate type, water depth and flow velocity in three shore channels in combination with species sensitivity distributions (SSDs) to predict habitat suitability for native and alien mussel species. SSDs allowed for the prediction of habitat suitability as a potentially occurring fraction (POF) of a species pool. High substrate type, water depth, and near-bottom flow velocity POFs were found for ≥ 70%, 100%, and 4–51% of the total shore channel area, respectively, suggesting that shore channels provide suitable habitat for both native and alien mussel species. To enhance the shore channels as habitat for native mussel species, we recommend increasing shallow areas dominated by fine (silt/clay) and sand substrate types with low near-bottom flow velocities (near 0 m/s). In contrast, the total area of hard substrate (e.g., boulders) in the shore channels should be reduced as it strongly favored invasive alien mussel species in our study. Future research should include additional abiotic parameters to enhance the habitat suitability predictions and compare the results for different riverine habitats.

National contributions to global ecosystem values - Laura E. Coristine; Sheila Colla; Nathan Bennett; Anja M. Carlsson; Christina Davy; Kimberley T.A. Davies; Brett Favaro; D.T. Tyler Flockhart; Kevin Fraser; Diane Orihel; Sarah P. Otto; Wendy Palen; et al. (Conservation Biology, 2019)
Current conservation templates prioritize biogeographic regions with high intensity ecosystem values, such as exceptional species richness or threat. Intensity‐based targets are an important consideration in global efforts, but they do not capture all available opportunities to conserve ecosystem values, including those that accrue in low intensity over large areas. We assess six globally‐significant ecosystem values—intact wilderness, freshwater availability, productive marine environments, breeding habitat for migratory wildlife, soil carbon storage, and latitudinal potential for range shift in the face of climate change—to highlight opportunities for high‐impact broadly‐distributed contributions to global conservation. Nations can serve as a cohesive block of policy that can profoundly influence conservation outcomes. Contributions to global ecosystem values that exceed what is predicted by a nation's area alone, can give rise to countries with the capacity to act as ‘conservation superpowers’, such as Canada and Russia. For these conservation superpowers, a relatively small number of national policies can have environmental repercussions for the rest of the world.

First records of metal concentrations in the Pacific oyster (Crassostrea gigas) from a Southwest Atlantic estuary - Noelia S. La Colla; Sandra E. Botté; Sandra M. Fiori; Eder P. Dos Santos; Ana C. Labudía (Environmental Geochemistry and Health, 2019)

Trade‐offs for data‐limited fisheries when using harvest strategies based on catch‐only models - Jessica C. Walsh; Cóilín Minto; Ernesto Jardim; Sean C. Anderson; Olaf P. Jensen; Jamie Afflerbach; Mark Dickey‐Collas; Kristin M. Kleisner; Catherine Longo; Giacomo Chato Osio; Elizabeth R. Selig; James T. Thorson; et al. (Fish and Fisheries, 2018)
Many of the world's fisheries are unassessed, with little information about population status or risk of overfishing. Unassessed fisheries are particularly predominant in developing countries and in small‐scale fisheries, where they are important for food security. Several catch‐only methods based on time series of fishery catch and commonly available life‐history traits have been developed to estimate stock status (defined as biomass relative to biomass at maximum sustainable yield: B/ B MSY ). While their stock status performance has been extensively studied, performance of catch‐only models as a management tool is unknown. We evaluated the extent to which a superensemble of three prominent catch‐only models can provide a reliable basis for fisheries management and how performance compares across management strategies that control catch or fishing effort. We used a management strategy evaluation framework to determine whether a superensemble of catch‐only models can reliably inform harvest control rules ( HCR s). Across five simulated fish life histories and two harvest‐dynamic types, catch‐only models and HCR combinations reduced the risk of overfishing and increased the proportion of stocks above B MSY compared to business as usual, though often resulted in poor yields. Precautionary HCR s based on fishing effort were robust and insensitive to error in catch‐only models, while catch‐based HCR s caused high probabilities of overfishing and more overfished populations. Catch‐only methods tended to overestimate B/ B MSY for our simulated data sets. The catch‐only superensemble combined with precautionary effort‐based HCR s could be part of a stepping stone approach for managing some data‐limited stocks while working towards more data‐moderate assessment methods.

Detachment rates of dreissenid mussels after boat hull-mediated overland dispersal - F. P. L. Collas; A. Y. Karatayev; L. E. Burlakova; R. S. E. W. Leuven (Hydrobiologia, 2018)

MPP+-Lesioned Mice: an Experimental Model of Motor, Emotional, Memory/Learning, and Striatal Neurochemical Dysfunctions - Mauricio P. Cunha; Francis L. Pazini; Vicente Lieberknecht; Josiane Budni; Ágatha Oliveira; Júlia M. Rosa; Gianni Mancini; Leidiane Mazzardo; André R. Colla; Marina C. Leite; Adair R. S. Santos; Daniel F. Martins; et al. (Molecular Neurobiology, 2017)

Creatine Prevents Corticosterone-Induced Reduction in Hippocampal Proliferation and Differentiation: Possible Implication for Its Antidepressant Effect - Francis L. Pazini; Mauricio P. Cunha; Dayane Azevedo; Julia M. Rosa; André Colla; Jade de Oliveira; Ana B. Ramos-Hryb; Patricia S. Brocardo; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2017)

Improving estimates of population status and trend with superensemble models - Sean C Anderson; Andrew B Cooper; Olaf P Jensen; Cóilín Minto; James T Thorson; Jessica C Walsh; Jamie Afflerbach; Mark Dickey‐Collas; Kristin M Kleisner; Catherine Longo; Giacomo Chato Osio; Daniel Ovando; et al. (Fish and Fisheries, 2017)
Fishery managers must often reconcile conflicting estimates of population status and trend. Superensemble models, commonly used in climate and weather forecasting, may provide an effective solution. This approach uses predictions from multiple models as covariates in an additional “superensemble” model fitted to known data. We evaluated the potential for ensemble averages and superensemble models (ensemble methods) to improve estimates of population status and trend for fisheries. We fit four widely applicable data‐limited models that estimate stock biomass relative to equilibrium biomass at maximum sustainable yield (B/ B MSY ). We combined these estimates of recent fishery status and trends in B/ B MSY with four ensemble methods: an ensemble average and three superensembles (a linear model, a random forest and a boosted regression tree). We trained our superensembles on 5,760 simulated stocks and tested them with cross‐validation and against a global database of 249 stock assessments. Ensemble methods substantially improved estimates of population status and trend. Random forest and boosted regression trees performed the best at estimating population status: inaccuracy (median absolute proportional error) decreased from 0.42 – 0.56 to 0.32 – 0.33, rank‐order correlation between predicted and true status improved from 0.02 – 0.32 to 0.44 – 0.48 and bias (median proportional error) declined from −0.22 – 0.31 to −0.12 – 0.03. We found similar improvements when predicting trend and when applying the simulation‐trained superensembles to catch data for global fish stocks. Superensembles can optimally leverage multiple model predictions; however, they must be tested, formed from a diverse set of accurate models and built on a data set representative of the populations to which they are applied.

Creatine, Similar to Ketamine, Counteracts Depressive-Like Behavior Induced by Corticosterone via PI3K/Akt/mTOR Pathway - Francis L. Pazini; Mauricio P. Cunha; Julia M. Rosa; André R. S. Colla; Vicente Lieberknecht; Ágatha Oliveira; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2016)

Oxygen can limit heat tolerance in freshwater gastropods: differences between gill and lung breathers - K. Remon Koopman; Frank P. L. Collas; Gerard van der Velde; Wilco C. E. P. Verberk (Hydrobiologia, 2016)

Antiviral properties from plants of the Mediterranean flora - G. Sanna; P. Farci; B. Busonera; G. Murgia; P. La Colla; G. Giliberti (Natural Product Research, 2015)

Synthesis of some new 2-amino-6-thiocyanato benzothiazole derivatives bearing 2,4-thiazolidinediones and screening of their in vitro antimicrobial, antitubercular and antiviral activities - Faiyazalam M. Shaikh; Navin B. Patel; Giuseppina Sanna; Bernardetta Busonera; Paolo La Colla; Dhanji P. Rajani (Medicinal Chemistry Research, 2015)

Isolation and anti-HIV-1 activity of a new sesquiterpene lactone from Calocephalus brownii F. Muell. - Magdy M.D. Mohammed; Lars P. Christensen; Paolo L. Colla (Natural Product Research, 2014)

Rapid range expansion of the invasive quagga mussel in relation to zebra mussel presence in The Netherlands and Western Europe - J. Matthews; G. Van der Velde; A. Bij de Vaate; F. P. L. Collas; K. R. Koopman; R. S. E. W. Leuven (Biological Invasions, 2014)

A review and critical analysis of the European situation of soilborne disease management in the vegetable sector - P. Colla; G. Gilardi; M. L. Gullino (Phytoparasitica, 2012)

Production of Nephrops norvegicus larvae in the Irish Sea - M. Dickey-Collas; R. P. Briggs; M. J. Armstrong; S. P. Milligan (Marine Biology, 2000)